Amino acid uptake in rust fungi - Struck, Christine (Frontiers in Plant Science, 2015)
The plant pathogenic rust fungi colonize leaf tissue and feed off their host plants without killing them. Certain economically important species of different genera such as Melampsora, Phakopsora, Puccinia or Uromyces are extensively studied for resolving the mechanisms of the obligate biotrophy. As obligate parasites rust fungi only can complete their life cycle on living hosts where they grow through the leaf tissue by developing an extended network of intercellular hyphae from which intracellular haustoria are differentiated. Haustoria are involved in key functions of the obligate biotrophic lifestyle: suppressing host defense responses and acquiring nutrients. This review provides a survey of rust fungi nitrogen nutrition with special emphasis on amino acid uptake. A variety of sequences of amino acid transporter genes of rust fungi have been published; however, transport activity of only three in planta highly up-regulated amino acid permeases have been characterized. Functional and immunohistochemical investigations have shown the specificity and localization of these transporters. Sequence data of various genome projects allowed identification of numerous rust amino acid tranporter genes. An in silico analysis reveals that these genes can be classified into different transporter families. In addition, genetic and molecular data of amino acid transporters have provided new insights in the corresponding metabolic pathways.